2010
DOI: 10.17221/165/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

ESBL and AmpC beta-lactamase-producing Enterobacteriaceae in poultry in the Czech Republic

Abstract: ABSTRACT:A major reason for resistance of Enterobacteriaceae to beta-lactam antibiotics is production of ESBLs and AmpC beta-lactamases. As their more detailed description in poultry is unavailable in the Czech Republic, the presented study aimed at assessing their occurrence and molecular characteristics. A total of 154 composite samples from broilers and 150 cloacal swabs from turkeys were examined. Production of ESBLs was detected in seven Escherichia coli isolates and AmpC enzymes in two E. coli isolates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…The prevalence was lower in comparison to those detected by Smet et al [11] 43% and Kolar et al [20] 25.9%. On the other hand, Blanc et al [23] reported the prevalence rate of E. coli isolates as AmpC β-lactamase producers was 6.7%.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The prevalence was lower in comparison to those detected by Smet et al [11] 43% and Kolar et al [20] 25.9%. On the other hand, Blanc et al [23] reported the prevalence rate of E. coli isolates as AmpC β-lactamase producers was 6.7%.…”
Section: Discussioncontrasting
confidence: 73%
“…On the contrary to these results, Kolar et al [20] described the most frequent ESBL types were SHV. In Spain, SHV-12-producing E. coli strains were then sporadically recovered in faecal samples from healthy chickens [24] .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Percentages of samples of food-producing animals or food in which ESBL-carrying E. coli isolates were detected varied from 0.2% to 40.1%, according to the country and the methodology used [ (Smet et al, 2009); Table 6]. Occurrences in the range of 10-40% were found when healthy poultry or pigs were analysed for the presence of ESBL-positive E. coli isolates in Portugal (Costa et al, 2009;Goncalves et al, 2010;Machado et al, 2008), Netherlands (Dierikx et al, 2010a), France (Girlich et al, 2007), and slightly lower percentages were identified in Czech Republic (Kolar et al, 2010). Moreover, ESBL-carrying E. coli isolates were found in most of pig and poultry farms tested in Spain , and also in five poultry farms tested in Italy (Bortolaia et al, 2010b).…”
Section: Prevalence Of Esbl-producing E Coli and Salmonella In Food-mentioning
confidence: 99%
“…Occurrence in the range of 10%-40% was found when healthy poultry or pigs were analysed for the presence of ESBL-positive E. coli isolates in Portugal (17), the Netherlands (7), France (11), and slightly lower percentages were identified in the Czech Republic (15). The recent data from Turkey shows that in 13.4% of E. coli isolated from meat (poultry and beef) ESBL production was confirmed by the phenotypic tests (1).…”
Section: Discussionmentioning
confidence: 99%